2021
DOI: 10.1002/pmrj.12682
|View full text |Cite
|
Sign up to set email alerts
|

Racial and ethnic amputation level disparities in veterans undergoing incident dysvascular lower extremity amputation

Abstract: Background The choice of incident amputation level can have a profound effect on clinical outcomes. Amputations at the transmetatarsal (TM) or transtibial (TT) levels result in greater preservation of function and mobility, whereas transfemoral (TF) amputations typically result in a greater adverse impact. Prior investigations have explored racial/ethnic and regional variation in incident amputation level. This study overcomes some of the methodological limitations seen in prior research through the use of a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
(129 reference statements)
0
2
0
Order By: Relevance
“…Black patients undergo LEA at higher rates than White patients; this finding has been shown for both veterans and civilians . Several possible explanations for this pervasive racial disparity have been proposed, including more aggressive atherosclerotic disease burden, patient presentation later in the course of disease, and a lower likelihood of being offered revascularization, which subsequently results in a higher rate of primary LEA .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Black patients undergo LEA at higher rates than White patients; this finding has been shown for both veterans and civilians . Several possible explanations for this pervasive racial disparity have been proposed, including more aggressive atherosclerotic disease burden, patient presentation later in the course of disease, and a lower likelihood of being offered revascularization, which subsequently results in a higher rate of primary LEA .…”
Section: Discussionmentioning
confidence: 96%
“…Black patients undergo LEA at higher rates than White patients; this finding has been shown for both veterans and civilians. 13,[17][18][19][20][21][22][23] Several possible explanations for this pervasive racial disparity have been proposed, including more aggressive atherosclerotic disease burden, 24-26 patient presentation later in the course of disease, 17,18,22,27 and a lower likelihood of being offered revascularization, which subsequently results in a higher rate of primary LEA. 17,[28][29][30][31] The findings from our study appeared to contradict some of these potential explanations; specifically, we found that African American or Black veterans were no less likely than White veterans to have an arterial blood flow assessment or revascularization in the year prior to LEA.…”
Section: Discussionmentioning
confidence: 99%